Bound on Poisson Approximation for the Street Light Problem via Stein-Chen Method: Chanokgan Sahatsathatsana, Noppakun Tongmol - Team, Support (Thai Journal of Mathematics, 2020)
In this paper, we are, consequently, interested in the problem of the number of bright sections of road and give the error estimation on poisson approximation of the number of bright sections of road with arbitrary probability by using Stein-Chen coupling method.